The accuracy and precision of interface pressure measuring devices: A systematic review. (October 2021) - Kokai, Orsolya; Kilbreath, Sharon L; McLaughlin, Patrick; Dylke, Elizabeth S
Introduction: Interface pressure measuring devices are used to assess the pressures exerted by compression. Their performance, however, has not been considered as a contributing factor to reported inconsistences in the application of compression. A systematic review was undertaken to investigate the performance of commercially available devices used to measure interface pressure. Methods: Six databases were searched identifying 17 devices, grouped into five sensor categories. Results: A range of methodologies assessed the devices' accuracy and precision, including method of pressure application, device calibration and type of surface used. No sensor category outperformed the others, however some individual sensors showed higher accuracy and/or precision compared to others. Two major factors influenced the performance of a number of sensors: the amount of applied pressure and the calibration method used. Conclusion: Inconsistences in the application of compression may reflect, in part, issues related to accuracy and precision of the devices used to assess compression.